Análise das demandas de informação encaminhadas pelos cidadãos à Ouvidoria-Geral do Estado de Minas Gerais: limitações e possibilidades - Cruz, Camila Campos da (2017)
This work consists of a study about the General Ombudsman's Office of the State of Minas Gerais (OGE), which emphasizes one of the main purposes of this body, namely, to listen to and treat the information demands made by citizens about the services provided by the State. The analysis presented here involves, firstly, a conceptual and historical discussion about public ombudsmen, with emphasis on the history and conception of the OGE, as well as on the use of new information and communication technologies (ICT). Then, the results obtained through the analysis of the description of the operation of the OGE, the characteristics of the demands of the information sent by the citizens to the organ and the survey carried out in the field through interviews with the Ombudsmen are presented and interpreted. Based on this information, this work proposes actions and measures that may contribute to the improvement of the internal procedures of the OGE, related to the demands of information sent by citizens to the organ.